2015
DOI: 10.1038/srep09737
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting expression patterns of coding and noncoding parts of the human genome upon oxidative stress

Abstract: Oxidative stress (OS) is caused by an imbalance between pro- and anti-oxidant reactions leading to accumulation of reactive oxygen species within cells. We here investigate the effect of OS on the transcriptome of human fibroblasts. OS causes a rapid and transient global induction of transcription characterized by pausing of RNA polymerase II (PolII) in both directions, at specific promoters, within 30 minutes of the OS response. In contrast to protein-coding genes, which are commonly down-regulated, this nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 75 publications
3
68
1
1
Order By: Relevance
“…The overexpression of oxidative processes is involved in CRF patients and remains the significant factors for elevated morbidity and mortality in these patients [29]. Another research has showed that the balance between the production of reactive oxygen species (ROS) and the availability of antioxidant enzymes, such as SOD, BUN, MDA and GSH-Px, is consequently critical for avoiding the tissue damage induced by OS [30, 31]. GSH-Px, as one of the markers of oxidative stress, is highly expressed in RIF rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of oxidative processes is involved in CRF patients and remains the significant factors for elevated morbidity and mortality in these patients [29]. Another research has showed that the balance between the production of reactive oxygen species (ROS) and the availability of antioxidant enzymes, such as SOD, BUN, MDA and GSH-Px, is consequently critical for avoiding the tissue damage induced by OS [30, 31]. GSH-Px, as one of the markers of oxidative stress, is highly expressed in RIF rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, it was recently shown that acute exposure to non‐toxic levels of H 2 O 2 resulted in the down‐regulation of many protein‐coding genes as well as in the generation of thousands of lncRNAs, mostly with promoter‐associated antisense lncRNAs transcripts. These lncRNAs, which are associated with polysomes, might represent a novel component of the (early) cellular stress responses (Giannakakis et al , ). Further studies will have to show the implications of these lncRNAs for the acute and possibly also prolonged cardiovascular response to ROS‐related stress conditions.…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…[3][4][5][6] Moreover, lncRNA expression exhibits strong temporal and spatial specificity, and the expression of the same lncRNA differs considerably during different developmental stages in the same | 4723 XU et al tissue or organ. [7][8][9][10] Abnormal lncRNA expression is closely related to many diseases, including cancer. Linc00152 is a class of lncRNA that is expressed uncontrollably in various tumor tissues, especially in malignant tumors of the digestive system, and is highly correlated with the formation, development, and metastasis of tumors.…”
Section: Introductionmentioning
confidence: 99%